OPTIMUM INFORMATION MANAGEMENT SECURITY - Ignatov , V. A.; Guziy , N. N. (Problems of Informatization and Management, 2005)
The paper shows that there are necessary and sufficient conditions for the construction of optimal information security management systems. A theorem on the optimal value of the cost of resources required to ensure a given level of information security is proved. Decision-making regarding the choice of protection resources is reduced to a typical problem of finding the extremum of a function of one variable. The practical significance of the statements of the theorem is emphasized by three consequences that play the role of practical recommendations.